Analyzing the Structure of the Maritime Silk Road Central City Network through the Spatial Distribution of Financial Firms. Issue 11 (1st September 2020) - Yin, Ruirui; Zhao, Bingxin; Zhang, Mengjie; Wang, Chengwei
ABSTRACT: The existing literature on the Maritime Silk Road focuses mainly on its scientific connotations, China's interconnection with countries along the Road, industrial linkage, investment, and trade, with little attention to the status, influence, and role of the central cities along its path. In an attempt to address this gap in the literature, this paper builds a central city network based on spatial distribution data on financial firms, designs an index system on the network's structural effect, and calculates the structural effects of the city network. The method and system of the indexes developed in this paper provide quantitative evidence for regional development strategies for the Maritime Silk Road and provide a valid research approach for studying regional associations.